PENGARUH PERBEDAAN TEKNIK PERONTOKAN PADI (Oryza Sativa L) TERHADAP MUTU FISIK BERAS KULTIVAR INPARI 44 - Mabruroh, Cinggih Rahmayanti; Budirokhman, Dodi; Amini, Zakiyah (Agroswagati : Jurnal Agronomi, 2024)
The aims of this study were : (1) To determine Effect of Different Rice Threshing Techniques on the Physical Quality of Rice Cultivar Inpari 44. (2) To determine the best threshing technique's effect on the physical quality of Inpari 44 cultivar rice. This research carried out in Pegagan Lor Village, Kapetakan District, Cirebon Regency, The research period starts in July-December 2023. The research method used is an experimental method without layout design with paired t-test. The treatment consisted of two factors and was repeated once using a power thresher and three times using gebotan. Threshing difference factor (P) consisting of 8 experimental units using gebots and 8 experiments using power thresher. The research results showed that the rice threshing technique using a power thresher had a real effect on head rice, broken rice, rice groats and milled yield.